LAYANAN BIMBINGAN KELOMPOK DALAM MENGEMBANGKAN KARAKTER PESERTA DIDIK DI MTSN - Zulvia Trinova Nova; Nini Nini; Aprizal Ahmad Afrizal; Aisyah Nurrahmah Aisyah (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2020)
AbstractThis research is motivated by the character of students who are not good, deviate, from the norms that apply in MTsN 2 Padang such as fighting against teachers, violating school rules, not greeting teachers when passing each other, not doing assignments given by teachers, pulling out, not listening when the teacher gives advice, fussing in class, playing around during prayer. The purpose of this study are: 1) to find out the planning of group guidance services in developing the character of students in MTsN 2 Padang. 2) to find out the implementation of group guidance services in developing the character of students in MTsN 2 Padang. 3) to find out the results and follow-up of group guidance services in developing student character in MTsN 2 Padang City. The method that I use in this research is descriptive qualitative method with qualitative descriptive research. To collect what is needed, the authors use data collection techniques through observation, interviews and documentation studies. The data processing techniques are data collection, data reduction, data presentation, conclusion or data verification. The results of the study are: a) group guidance service planning is done by identifying students' problems, assigning group members, determining the time of service implementation, and completing the administration of group guidance service implementation, b) the implementation of group guidance services carried out group guidance related material about the character of students, in developing the character of students. c) the results of the implementation of group guidance services namely interviews with students related to group guidance services in developing students' character and providing follow-up.